Effects of dimethyl sulfide pertubations in ACCESS-UKCA climate simulations - Fiddes, Sonya (Zenodo, 2018)
This dataset includes 10-year averages of cloud, radiation, precipitation and aerosol/chemistry fields from the Australian Community Climate and Earth System Simulator (ACCESS) United Kingdom Chemistry and Aerosol (UKCA) model. This model includes a sophisticated chemistry and aerosol scheme GLOMAP-mode (Mann et al. 2012). The model runs were used to evaluate cloud, radiation and precipitation of this model and to quantify the role of dimethyl sulfide in the global climate system. Simulations were run from 2000-2009, including a control run and two experimental runs that look at the climate response to large changes in oceanic dimethyl sulfide (DMS). The horizontal grid resolution is 1.25 degree latitude, 1.85 degree longitude, with 85 vertical levels, SSTs and sea ice were prescribed to AMIP SSTs and the model was nudged to ERA-Interim. Emissions were prescribed to ACCMIP pre-2000, and RCP6.0 post 2000. Three simulations were performed where the oceanic surface concentrations of DMS were altered: Control -- a control run using the Lana et al. (2011) oceanic DMS data set zero_DMS -- a run in which oceanic dimethyl sulfide is removed (set to zero) max_DMS -- a run in which oceanic dimethyl sulfide is set to its latitudinal maximum. A detailed description of the model and the experimental set up can be found in Fiddes et al. 2018 The model simulations were run on the National Computing Infrastructure (NCI) facilities. Python 2.7 was used to do the analysis of model output. The simulations and analysis were performed by Sonya Fiddes as part of her PhD with the ARC Centre of Excellence for Climate System Science research program: "The effects of tropical convection on Australia's climate". Preferred citation: Fiddes, S., 2018: Effects of dimethyl sulfide pertubations in ACCESS-UKCA climate simulations v1.0. NCI National Research Data Collection , doi:10.4225/41/5b35c03d52de9 Access to the data is via the NCI geonetwork record in related identifiers, details are also provided in the readme file.